Radiant Energy During Clear Weather in the Growing Season at Poste-de-la-Baleine (Great Whale), Nouveau-Québec - Wilson, Cynthia (Cahiers de géographie du Québec, 1976)
In a previous article, regression coefficients were determined for the major surface types during clear weather at Poste-de-la-Baleine, to permit estimates of net radiation given the incoming solar radiation. In the present complementary study :(i) a curve is set up to provide a quick estimate of the incoming solar radiationfluxes ini clear weather ; (ii) daily coefficients of atmospheric transmissivity are given for characteristicclear-weather synoptic situations ; (iii) an attempt is made to define a clear hour in terms of bright sunshine andhourly weather observations, to assess the frequency and duration of clearweather in the growing season for which all these radiant energy curves arevalid ; (iv) a brief climatology of clear weather is presented for the period 1971 to 1975.The information provided in these two papers is relevant in ecology and resource management, and in the development of solar heating and greenhouses, but it applies strictly to the coastal zone.